2015
DOI: 10.2147/opth.s87972
|View full text |Cite
|
Sign up to set email alerts
|

Novel single-nucleotide polymorphisms in the calsequestrin-1 gene are associated with Graves’ ophthalmopathy and Hashimoto’s thyroiditis

Abstract: BackgroundThe eye disorder associated with Graves’ disease, called Graves’ ophthalmopathy (GO), greatly reduces the quality of life in affected patients. Expression of the calsequestrin (CASQ1) protein in thyroid tissue may be the trigger for the development of eye muscle damage in patients with GO. We determined the prevalence of rs74123279, rs3747673, and rs2275703 single-nucleotide polymorphism (SNPs) in patients with autoimmune thyroid disorders, GO, Graves’ hyperthyroidism (GH), or Hashimoto’s thyroiditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In previous publications 43 , 45 , 46 we suggested that CASQ1 gene SNPs rs3838216, rs74123279, and rs2275703 are possible genetic markers for GO and HT, in addition to those that are already known. They are potentially pathogenic genetic markers for the eye muscle component of GO.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous publications 43 , 45 , 46 we suggested that CASQ1 gene SNPs rs3838216, rs74123279, and rs2275703 are possible genetic markers for GO and HT, in addition to those that are already known. They are potentially pathogenic genetic markers for the eye muscle component of GO.…”
Section: Discussionmentioning
confidence: 92%
“…1) MassARRAY SNP analysis using iPLEX technology of SEQUENOM has been described in detail in previous publications of this laboratory. 43 , 45 , 46 2) Functional analysis: T4, T3, thyroid receptors antibodies (TRAB), TSI, TSHr, TG antibody, and TPO antibody were measured by established radio immunoassay methods in pathology laboratories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So these results strongly suggest that the occurrence of thyroid dysfunction in teenagers can be caused by family history, which means the genetic background. The eye disorder associated with AITD, called thyroid-associated ophthalmopathy, drastically reduces the quality of life in affected patients and even contributes to the disability of patients [ 20 ]. Enormous amounts of documents have shown that TAO is a complex disease with multifaceted mechanism including smoking history, thyroid dysfunction, and positive TRAb [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several susceptibility genes for Graves’ ophthalmopathy have been proposed over the years based on small case–control association studies. These include CTLA-4 , tumor necrosis factor-α ( TNF- α), intercellular adhesion molecule-1 ( ICAM-1 ), interferon-γ ( IFN- γ) ( 8 ), insulin-like growth factor-1 receptor ( IGF-1R ) ( 9 ), suppressor of cytokine signaling 3 ( SOCS3 ) ( 10 ), thyroid peroxidase ( TPO ) ( 11 ), calsequestrin 1 ( CASQ1 ) ( 12 ), cysteine-rich angiogenic inducer 61 ( CYR61 ), zinc finger protein 36 C3H type homog mouse ( ZFP36 ), and stearoyl-coenzyme A desaturase ( SCD ) ( 13 ). However, none of the Graves’ ophthalmopathy specific genes have been confirmed.…”
Section: Introductionmentioning
confidence: 99%